Pengaruh Kecepatan Potong Terhadap Kekasaran Benda Kerja Baja AISI 1018 pada Proses Pembubutan Kering - Yonathan Farrel Marcelino; Muhammad Sobron Yamin Lubis; Rosehan Rosehan (CV. IRA PUBLISHING, 2025)
Cutting speed is one of the crucial parameters in the turning process that significantly affects the final quality of the workpiece surface. This study aims to evaluate the impact of cutting speed variations on the surface roughness level of AISI 1018 steel. The machining process was carried out using a chisel with a tip radius of 1.2mm, and the cutting speed was varied at three levels, namely 42m/min, 66m/min, and 105m/min. Surface roughness measurements were carried out using a Surface Roughness Tester. The experimental results showed that increasing cutting speed tended to decrease surface roughness. The lowest roughness value of 2.224 μm was obtained at a cutting speed of 105 m/min. This phenomenon occurs because at higher cutting speeds, cutting forces and vibrations are reduced, so that the machining process becomes more stable and produces better surface quality. This study shows that cutting parameters play an important role in optimizing the final results of conventional turning processes.